Different frequencies of human scalp-recorded theta activity may index integration of activity in distinct recurrent cortico-subcortical mnemonic networks - Haddon, Inanna K.; King, Rohan O. C.; Taylor, Dylan A.; Bell, Jodie N.; Murray, Jasmine E. B.; van der Meer, Meghan; Erb, Christopher D.; Kirk, Ian J. (Frontiers in Behavioral Neuroscience, 2025)
It is now well-accepted that differing frequencies of neuro-oscillations support the selection, quantising, and pacing of information around different circuits in the brain. Another related function of neuro-oscillations, for which the frequency of oscillation is again critical, is to allow for integration of neural activity across differing spatial scales. In this short review, we discuss the degree to which human scalp-recorded EEG occurring in the theta-range (4-8 Hz) can be used to infer activation of mnemonic circuits involving the hippocamps and diencephalon (Papez loops), as well as in the neocortical areas the activity is directly recorded from. We also discuss the potential role of theta-range frequency modulation in the selection of specific mnemonic circuits. In light of the foregoing, we suggest that the frequency at which theta is occurring within and between cognitive tasks should be reported more thoroughly than it generally is. Finally, we suggest that assessing disruptions in frequency modulation of theta-range oscillations is a potentially valuable biomarker for disorders such as Alzheimer’s disease.